2020
DOI: 10.1371/journal.pone.0229187
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioural cue reactivity to alcohol-related and non-alcohol-related stimuli among individuals with alcohol use disorder: An fMRI study with a visual task

Abstract: Patients with alcohol use disorder (AUD) have difficulty controlling their alcohol cravings and thus exhibit increased use and early relapse. Although patients tend to respond more strongly to alcohol-related images than to non-alcohol-related images, few researchers have examined the factors that modulate cravings. Here, we examined whole-brain blood oxygen level-dependent (BOLD) responses to behavioural cues in individuals with AUD and in healthy controls (HCs). The participants included 24 patients with AUD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In line with previous findings, AUD patients exhibited impairments in the insula and precuneus regions (Fukushima et al, 2020 ; Bordier et al, 2021 ). Recent fMRI studies have demonstrated that AUD can enhance activation in the insula, inferior frontal gyrus, and precuneus (Noori et al, 2016 ; Quaglieri et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous findings, AUD patients exhibited impairments in the insula and precuneus regions (Fukushima et al, 2020 ; Bordier et al, 2021 ). Recent fMRI studies have demonstrated that AUD can enhance activation in the insula, inferior frontal gyrus, and precuneus (Noori et al, 2016 ; Quaglieri et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…The visuospatial network has been linked to cue reactivity in the context of AUD. In one study, Fukushima and colleagues found stronger fMRI BOLD response in the left precuneus among individuals with AUD, compared to controls, when they were exposed to images depicting drinking alcohol, and opposite results when exposed to images of drinking juice 66 . Another study looked at the connection between the visuospatial network and parietal regions, and found weaker resting-state connectivity to the visuospatial network in individuals with AUD, compared to controls, implying potential deficits in memory encoding and insufficient visuospatial information for well-controlled movements 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Many neuroimaging studies have reported brain activation in alcohol craving (Modell and Mountz, 1995;George et al, 2001;Heinz et al, 2004;Karch et al, 2015;Fukushima et al, 2020). Acupuncture at Shenmen (HT7) acupoint on the heart channel is frequently used to treat mental and psychiatric disorders Cue-elicited alcohol craving was assessed using a 10-point Likert scale.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have investigated brain regions involved in alcohol cue-elicited craving in patients with alcohol use disorder (Modell and Mountz, 1995;George et al, 2001;Heinz et al, 2004;Karch et al, 2015;Fukushima et al, 2020). These finding indicated brain regions activated by cues are associated with reward, memory, cognition and emotion (Myrick et al, 2004;Filbey et al, 2008;Cai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%